2017
DOI: 10.6007/ijarbss/v7-i6/3031
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption Practices of Students through Practice-Oriented Approach of Education for Sustainable Development

Abstract: Sustainable consumption practice is an effective approach to educating the younger generation in how to achieve sustainability in the future in agreement with sustainable development principles. This article aims to examine Education for Sustainable Development (ESD) knowledge and sustainable consumption practices. This study has three areas of focus, namely, (i) to study the difference between ESD knowledge and sustainable consumption practices among genders; (ii) to assess the difference between ESD knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 4 publications
0
14
1
Order By: Relevance
“…Some studies that examined systems or knowledge of environmental issues found an insignificant relationship between knowledge and pro-environmental behavior [54,62,74,92]. Ahmad and Ariffin [30] and Mahat et al [93] stated that environmental knowledge does not necessarily result in pro-environmental actions. The results of Paҫo and Lavrador [26] pointed to the lack of relationship between knowledge and behavior.…”
Section: The Impact Of Environmental Knowledge and Ecological Worldview On Pro-environmental Behaviormentioning
confidence: 99%
“…Some studies that examined systems or knowledge of environmental issues found an insignificant relationship between knowledge and pro-environmental behavior [54,62,74,92]. Ahmad and Ariffin [30] and Mahat et al [93] stated that environmental knowledge does not necessarily result in pro-environmental actions. The results of Paҫo and Lavrador [26] pointed to the lack of relationship between knowledge and behavior.…”
Section: The Impact Of Environmental Knowledge and Ecological Worldview On Pro-environmental Behaviormentioning
confidence: 99%
“…These findings are due to the fact that awareness and extensive research are playing a very important role in helping educational policy makers reshape their curriculum according to the new demands of the growing and well-aware world. The awareness for a sustainable environment has been the key factor in the universities and colleges while delivering the content of the studies ( Godemann et al, 2014 ; Sivapalan et al, 2016 ; Mahat et al, 2017 ; Badea et al, 2020 ). The findings of the study are in accordance with the previous studies conducted by many authors.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting the behaviors that are unsustainable for the environment can help in decreasing the deterioration of the surrounding at the mass level; hence, to shape the behaviors of people education is necessary ( Shephard, 2015 ; Caniglia et al, 2018 ; Calvo et al, 2020 ; Lister et al, 2021 ). Educating the younger generation in such a way creates the attitudes, responsibilities, skills, and understanding of the concept of environmental stability in their minds as children ( Mahat et al, 2017 ; Badea et al, 2020 ). It has also been argued that as adolescents in their secondary schools, it is easier to implant the values since they are more receptive and can easily develop sustainable behavior and also induce this in others ( Calvo et al, 2020 ; Nie et al, 2020 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…On the contrary, some studies indicated that university students did not convert environmental knowledge into environmental actions. Empirical investigation revealed that students exhibiting a high level of environmental knowledge did not report high practices of green behaviors (Ahamad & Ariffin, 2018; Mahat, Hashim, Nayan, Saleh, & Haron, 2017). Therefore, the role of environmental knowledge in promoting PEBs can vary, depending on different situations and contexts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%